2008
DOI: 10.1037/0735-7044.122.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Differential genetic regulation of motor activity and anxiety-related behaviors in mice using an automated home cage task.

Abstract: Traditional behavioral tests, such as the open field test, measure an animal's responsiveness to a novel environment. However, it is generally difficult to assess whether the behavioral response obtained from these tests relates to the expression level of motor activity and/or to avoidance of anxiogenic areas. Here, an automated home cage environment for mice was designed to obtain independent measures of motor activity levels and of sheltered feeding preference during three consecutive days. Chronic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Similar patterns of intermittent locomotion have been observed in rodents exploring novel laboratory environments (42) and are also common in natural environments (43). Despite the prevalence of such movement patterns, procedures for capturing their basic features had not previously been developed for home cage behavioral assessment (1,(6)(7)(8)(9)(10)(11)(12)(13)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Similar patterns of intermittent locomotion have been observed in rodents exploring novel laboratory environments (42) and are also common in natural environments (43). Despite the prevalence of such movement patterns, procedures for capturing their basic features had not previously been developed for home cage behavioral assessment (1,(6)(7)(8)(9)(10)(11)(12)(13)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 62%
“…The functions and interactions of these systems result in the coordinated organization of multiple behaviors (3-5). Although several sophisticated approaches for automated behavioral data collection and home cage monitoring exist, they do not employ algorithms that quantitatively capture the rich temporal and spatial structure of diverse behaviors that occur over multiple time scales (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).As a first step in examining this structure, we made use of the observation that in natural environments animals typically alternate between two major discrete states, active and inactive (20)(21)(22). During active states (ASs), animals engage in behaviors such as foraging and patrolling within a regularly traversed home range.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By partitioning the genome into a panel of new inbred strains with single CSs, (one strain for each chromosome), unique experimental designs and considerable statistical power are possible to accelerate the detection of quantitative trait loci (QTLs) with small effect sizes [Singer et al, 2004]. Several published studies demonstrate the considerable utility of these strains and new applications for CS strains continue to be discovered [Singer et al, 2004;Hill et al, 2006;Kas et al, 2008]. Compulsivity was assumed to be mimicked by continuous and repetitive wheel running during the 2 hr of food availability as it expresses the inability to stop wheel running despite the more appealing food availability.…”
Section: Introductionmentioning
confidence: 99%
“…By using gene expression analysis, Hitzemann et al (2003) were able to identify Kcnj9 as the most likely candidate gene in this region. In addition, several other likely positions for loci on chromosome 1 are found that affect motor activity levels (100 Mb, de Ledesma et al 2006190 Mb, Singer et al 2004 Mb, Kas et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%